UPAYA GURU DALAM MENGATASI KESULITAN MEMBACA SISWA DI SD NEGERI 41 KARANG TANGAH - Sevildia, Vindia; Dwiana, Ari Aprillia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
In facing the challenges students face in reading, teachers need to be proactive in providing guidance to help them overcome obstacles that hinder the learning process. This research aims to explain the reading problems faced by students and the teachers' efforts to solve them in class I-VI of SDN 41 Karang Tangah. The method applied in this research is a qualitative approach. Researchers used various data collection techniques including observation, interviews and document analysis involving research subjects consisting of class I-VI homeroom teachers and class I-VI students at SDN 41 Karang Tangah. The research results showed that there were class I-VI students who experienced difficulties in reading, such as lack of reading fluency, frequent mistakes, difficulty in distinguishing similar letters, and errors in pronouncing words or sound symbols. The efforts taken by teachers to overcome the reading difficulties of class I-VI students at SDN 41 Karang Tangah, have been quite effective. Teachers use interesting and interactive learning methods, such as picture letter books, and strengthen students' self-confidence and motivation through praise. In addition, teachers do not blame students and provide special remedial programs to improve their reading skills.